KUALITAS FISIK PELET AYAM BROILER PERIODE AKHIR DENGAN PENAMBAHAN FESES TERNAK DAN BAHAN PEREKAT YANG BERBEDA - Indra Rahmana; Dewi Ananda Mucra; Dewi Febrina (State Islamic University of Sultan Syarif Kasim Riau, 2016)
The study aimed to know the physical quality of pellets for finisher period added different feces and adhesive matter. The experiment design was randomized complety block design factorial (RCBD) with two factors and three replications. The first factor was feces (goat feces, cattle feces, buffalo feces) and the second factor was adhesive matter (tapioca flour, eeg white, sago flour). Physical observation were water content, specific gravity, bulk density, compressed bulk density, angle of repose, and the durability of pellet. The result showed that addition type feces influenced water content, specific gravity, bulk density, compressed bulk density, angle of repose and the durability of pellet form. The result showed that addition adhesive matter influenced bulk density, compressed bulk density, the durability of pellet form.Interaction the addition of cattle feces and different adhesive matter in water content, specific gravity, compressed bulk density, angle of repose and the durability of pellet. Interaction buffalo feces and tapioca flour best quality.